2016
DOI: 10.5606/archrheumatol.2016.5628
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione-S-Transferase Variants are not Associated With Increased Carotid Intima-Media Thickness in Turkish Familial Mediterranean Fever Patients

Abstract: Objectives: This study aims to evaluate the carotid intima-media thickness (CIMT) in patients diagnosed with familial Mediterranean fever (FMF) and investigate whether there is a relationship between glutathione-S-transferase (GST) gene polymorphisms and CIMT. Patients and methods: Sixty FMF patients (17 males, 43 females; mean age: 31.43±11.36 years; range 18 to 45 years) and 60 healthy controls (22 males, 38 females; mean age: 29.8±5.82 years; range 18 to 40 years) were enrolled in this study. Polymerase cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…Other studies that were done in adults with FMF matched our results, such as the study done by Gürbüz et al [16]. Another study that was conducted by Akdogan et al [17] showed that the mean CIMT in patients was higher than the mean in the controls 0.06 ±0.07 and 0.05 ±0.07 respectively.…”
Section: Discussionsupporting
confidence: 89%
“…Other studies that were done in adults with FMF matched our results, such as the study done by Gürbüz et al [16]. Another study that was conducted by Akdogan et al [17] showed that the mean CIMT in patients was higher than the mean in the controls 0.06 ±0.07 and 0.05 ±0.07 respectively.…”
Section: Discussionsupporting
confidence: 89%
“…Renal or submucosal rectal biopsies are used for showing amyloidosis deposition in tissues. Recently, there have been studies in the literature reporting that secondary findings of amyloidosis deposition can be shown in a non‐invasive manner by ultrasonography and Doppler, and amyloid‐dependent organ failure can be determined 11,12 . However, there are not any sufficient studies evaluating amyloidosis deposition by shear wave elastography (SWE) in the literature, and the studies are limited to the thyroid and salivary glands.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there have been studies in the literature reporting that secondary findings of amyloidosis deposition can be shown in a non-invasive manner by ultrasonography and Doppler, and amyloid-dependent organ failure can be determined. 11,12 However, there are not any sufficient studies evaluating amyloidosis deposition by shear wave elastography (SWE) in the literature, and the studies are limited to the thyroid and salivary glands. In our study, we evaluated the phenotype-genotype correlation between tissue parenchyma stiffness and vascular resistances by MEFV gene mutation analysis.…”
mentioning
confidence: 99%